Lateral Squats Significantly Decrease Sprint Time in Collegiate Baseball Athletes - Jason B. White; Trevor P. Dorian; Margaret T. Jones (MDPI AG, 2016)
The purpose was to examine the effect of prior performance of dumbbell lateral squats (DBLS) on an agility movement-into-a-sprint (AMS) test. Twelve collegiate, resistance-trained, baseball athletes participated in three sessions separated by three days. Session One consisted of AMS baseline test, DBLS 5-RM test, and experimental protocol familiarization. Subjects were randomly assigned the protocol order for Sessions Two and Three, which consisted of warm up followed by 1-min sitting (no-DBLS) or performing the DBLS for 1 × 5 repetitions @ 5RM for each leg. Four minutes of slow recovery walking preceded the AMS test, which consisted of leading off a base and waiting for a visual stimulus. In reaction to stimulus, subjects exerted maximal effort while moving to the right by either pivoting or drop stepping and sprinting for 10 yards (yd). In Session Three, subjects switched protocols (DBLS, no-DBLS). Foot contact time (FCT), stride frequency (SF), stride length (SL), and 10-yd sprint time were measured. There were no differences between conditions for FCT, SF, or SL. Differences existed between DBLS (1.85 ± 0.09 s) and no-DBLS (1.89 ± 0.10 s) for AMS (p = 0.03). Results from the current study support the use of DBLS for performance enhancement prior to performing the AMS test.